A novel caspase-6 from sea cucumber Holothuria leucospilota: Molecular characterization, expression analysis and apoptosis detection. Issue 80 (September 2018) - Yan, Aifen; Ren, Chunhua; Chen, Ting; Huo, Da; Jiang, Xiao; Sun, Hongyan; Hu, Chaoqun
Abstract: In this study, a novel caspase-6 named HLcaspase-6 was identified from sea cucumber Holothuria leucospilota . The full-length cDNA of HLcaspase-6 is 2195 bp in size, containing a 126 bp 5′-untranslated region (UTR), a 1043 bp 3′-UTR and a 1026 bp open reading frame (ORF) encoding a protein of 341 amino acids with a deduced molecular weight of 38.57 kDa. HLcaspase-6 contains the common signatures of the caspase family, including the conserved pentapeptide motif QACRG, as well as the P20 and P10 domains. In addition, HLcaspase-6 contains a short pro-domain. HLcaspase- 6 mRNA is ubiquitously expressed in all tissues examined, with the highest transcript level in the intestine, followed by coelomocytes. In in vitro experiments, the expression of HLcaspase- 6 mRNA in coelomocytes was significantly up-regulated by lipopolysaccharides (LPS) or polyriboinosinic-polyribocytidylic acid [poly (I:C)] challenge, suggesting that HLcaspase-6 might play important roles in the innate immune defense of sea cucumber against bacterial and viral infections. Moreover, we further confirmed that overexpression of HLcaspase-6 could induce apoptosis and activate the p53 signal pathway. Highlights: We identified a caspase-6 from tropical sea cucumber H. leucospilota. The common signatures of caspase family can be found in H. leucospilota caspase-6. HLcaspase- 6 mRNA is widely expressed and up-regulated by immune challenge in coelomocytes. Overexpression of HLcaspase-6 can induce apoptosis in HEK293T cells. HLcaspase-6 can activate the p53 signal pathway.